Rabbis in Israel, Public Relations and Advertising - Yoel Cohen (Religion and Social Communication)
This article discusses public relations (PR) and advertising in the work of the rabbi in Israel. The rabbi’s influence is felt within the religious population such as through the Sabbath sermon from the synagogue pulpit to congregants, but the media is an additional channel to spreading the rabbi’s religious message. The traditional, and secular Israeli Jewish population—as distinct from religiously observant (25 per cent of the Israeli Jewish population)—have no regular daily or weekly interaction with the synagogue, which raises the question of the rabbis using extra-synagogual channels to reach them, notably mass media channels.